ANALISIS FAKTOR-FAKTOR PERSEPSIÂ YANG BERHUBUNGAN DENGAN KEBUTUHAN AKAN PERUBAHAN DARI PERAWATÂ DI RSUD SIDOARJO JAWA TIMUR - Santoso, Windu (JURNAL KEPERAWATAN BINA SEHAT, 2013)
Changes are happened surround us and is percieved as a “compulsory menu” for every organization to face dynamic and competitive situation nowdays. The change and the maintenance of change process are needed in nursing practice and nursing services. This study used a descriptive correlational with cross sectional approach. The aim is to examine the relationship between perception factors and the needs of change among nurses at RSUD Sidoarjo East Java. The population were 345 staff nurses who were which was graduated from SPK, D3 and S1 of Nursing. The sample size was 221 staff nurse obtained as a total population. This research found that there is a correlation between the nurse perception on the role of reformer agent and the needs of change (p=0,002), the nurse perception on resistent resources and the needs of change (p=0,008), the nurse perception on change succes factors and the needs of change (p=0,029). A multivariate analysis showed that the nurse perception on role as a reformer agent represents the most significantly correlated with needs of change (p=0,002). Further this research recomends that to conduct a change for better nursing services, it needs to share the vision to all management and staff, from planning until implementation of change, therefore it could be optimized the change process it self. In Addition a reward system is required either material or non material, such as the opportunity to attend the higher education, to attend the seminar or training, voucher given to the nurse who implements change in order to improved the quality of nursing services, so that an improvement of services quality can be achieved.Keyword: need of change, perception, resistence resources, success factors.